The role of the Francisco Javier Clavijero Botanic Garden (Xalapa, Veracruz, Mexico) in the conservation of the Mexican flora - Díaz-Toribio, Milton; Luna, Victor; Vovides, Andrew (Instituto de Ecología, A.C., 2021)
Background and Aims: There are approximately 3000 botanic gardens in the world. These institutions cultivate approximately six million plant species, representing around 100,000 taxa in cultivation. Botanic gardens make an important contribution to ex situ conservation with a high number of threatened plant species represented in their collections. To show how the Francisco Javier Clavijero Botanic Garden (JBC) contributes to the conservation of Mexican flora, we asked the following questions: 1) How is vascular plant diversity currently conserved in the JBC?, 2) How well is this garden performing with respect to the Global Strategy for Plant Conservation (GSPC) and the Mexican Strategy for Plant Conservation (MSPC)?, and 3) How has the garden’s scientific collection contributed to the creation of new knowledge (description of new plant species)?Methods: We used data from the JBC scientific living collection stored in BG-BASE. We gathered information on species names, endemism, and endangered status, according to national and international policies, and field data associated with each species. Key results: We found that 12% of the species in the JBC collection is under some risk category by international and Mexican laws. Plant families with the highest numbers of threatened species were Zamiaceae, Orchidaceae, Arecaceae, and Asparagaceae. We also found that Ostrya mexicana, Tapirira mexicana, Oreopanax capitatus, O. echinops, and O. xalapensis are highly threatened species representative of cloud forest currently in the collection. Conclusions: The conservation and scientific utility of the JBC collection is reflected in the exceptional accession data and the description of 24 new plant species. Having a significant number of threatened plant species in its ex situ collection, the JBC contributes to the implementation of the GSPC, particularly Target 8, as well as the implementation of the MSPC.